Sex-Specific Prevalence of Diabetes and Cardiovascular Risk Factors in the Middle-Aged Population of China: A Subgroup Analysis of the 2007-2008 China National Diabetes and Metabolic Disorders Study. - Shi Bu (PLoS ONE, 2015)
The sex difference in the prevalence rates of diabetes and cardiovascular diseases (CVDs) among the middle-aged population in China remain largely unknown. Therefore, we analyzed differences in the prevalence of diabetes, self-reported CVDs, and some CVD risk factors among men and women in the middle-aged population (30-49 years) and in individuals aged 50 years and older using data from the China National Diabetes and Metabolic Disorders Study of 2007-2008. Middle-aged men appeared to have significantly a higher prevalence of diabetes and self-reported CVDs than middle-aged women (8.07% vs 5.06% for diabetes, P < 0.001; 0.64% vs 0.22% for CVDs, P < 0.001). Men also showed higher rates of central obesity, hypertension, and dyslipidemia than women (all P < 0.01). Compared with women, men were more likely to drink alcohol and smoke cigarettes but less likely to be under diet control. The sex-specific differences in prediabetes, CVD, and CVD risk factors between men and women were diminished or even reversed in the population aged 50 years and older. No sex-specific differences were found in the prevalences of a family history of diabetes, coronary heart disease, and hypertension (P > 0.05) in middle-aged population. Specific strategies to reduce modifiable risk factors for the prevention and control of diabetes and CVD may be warranted in this population.